The current state of forensic imaging – perspectives - Fabrice, Dedouit; Mathilde, Ducloyer; Jamie, Elifritz; Natalie, L. Adolphi; Grace Yi-Li, Wong; Summer, Decker; Jonathan, Ford; Yanko, Kolev; Michael, Thali (Springer Nature, 2025)
This fourth part of the review of the current state of forensic imaging describes the future potential in uence of arti cial intelligence in forensic imaging. In addition to this important point, training in forensic imaging is discussed in detail, as are the documentation possibilities o ered by non-conventional imaging tools such as photography, photogrammetry, 3D surface scanning and 3D print casts.